Adsorption of Copper (II) from aqueous medium in fixed-bed column by kenaf fibres. - Che Man, Hasfalina; Abdullah, Luqman Chuah; Rahmati Zadeh, Maryam; Mohd Yusoff, Mohd Rashid (2012)
The adsorption of Copper (II) from aqueous solution by kenaf (Hibiscus cannabinus, L) fibres was investigated in fixed-bed column. The effect of selected operating parameters such as flow rate and bed depth was evaluated. The breakthrough data fitted well to Bed Depth Service Time (BDST) and Thomas models with high correlation coefficient, Rtwo2≥ 91. The highest bed capacity was obtained at 47.27 mg/g using 100 mg/L of initial Copper (II) and 6 mL/min flow rate. The results showed that kenaf fibres can be an effective adsorbent for Copper (II) removal.